Associations between HbA1c and depressive symptoms in young adults with early-onset type 1 diabetes. (May 2015) - Bächle, Christina; Lange, Karin; Stahl-Pehe, Anna; Castillo, Katty; Holl, Reinhard W.; Giani, Guido; Rosenbauer, Joachim
Highlights: Depressive symptoms are frequent in young adults with early-onset type 1 diabetes. 5.0%/2.5% of the women/men met the DSM-5 criteria for a major depressive syndrome. HbA1c was associated differently with depressive symptoms among men and women. Summary: Objective: This study sought to evaluate the associations between metabolic control and each DSM-5 (Diagnostic and Statistical Manual, fifth edition) symptom of depression among young women and men with early-onset long-duration type 1 diabetes. Methods: The data of 202 18–21-year-old patients with type 1 diabetes from a population-based, nationwide survey (40.1% male) with a mean age of 19.4 (standard deviation 0.9) years, a mean HbA1c level of 8.3% (1.6%) (i.e., 67 [17.5] mmol/mol), and a mean diabetes duration of 15.7 (1.0) years were included. The German version of the Patient Health Questionnaire (PHQ-9) was used to assess depression symptoms. For each PHQ-9 depressive symptom, the mean HbA1c values of screening-positive and screening-negative patients were compared via t -test. The associations between HbA1c levels and depressive symptoms were analyzed using multiple linear regression analyses and stepwise adjustments for individual, socioeconomic and health-related covariates. Results: Exactly 43.0% and 33.3% of female and male participants reported at least one depressive symptom, and 5.0% and 2.5% met the DSM-5 criteria for major depressive syndrome. HbA1c levels increased with psychomotor agitation/retardation (women), overeating/poor appetite (men/women), lethargy (men), and sleep difficulty (men). Overeating/poor appetite, lethargy, and total PHQ-9 score (per score increase by one) were associated with increased HbA1c levels of 1.10, 0.96 and 0.09 units (%), respectively. Conclusions: The associations between depressive symptoms and HbA1c levels vary by symptom and sex. Differentiating the symptoms of depression and targeted interventions might help to improve metabolic outcomes in young adults with early-onset type 1 diabetes and depression.